Exploring Innovative Strategies For Patient-Centered Care In The Nursing Profession - Tamli, Nabin; Sain, Manoj (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This article explores the integration of technology, interdisciplinary collaboration, evidence-based practice, and improved resources and training in the nursing profession as innovative strategies for advancing patient-centered care. The integration of technology has revolutionized healthcare delivery, enabling improved access, communication, and empowerment for patients. Electronic health records (EHRs), telehealth platforms, and mobile health applications facilitate personalized care planning, remote patient monitoring, and patient education. Evidence-based practice is a cornerstone of patient-centered care, promoting the use of the best available evidence in clinical decision-making. By integrating research findings and evidence-based guidelines into practice, nurses can deliver high-quality care that is tailored to individual patient needs. Evidence-based practice enhances patient safety, improves outcomes, and increases patient satisfaction. Improved resources and training are essential for supporting patient-centered care. Adequate staffing levels, patient-centered infrastructure, and ongoing professional development opportunities enable nurses to deliver care that is responsive to individual patient needs. By investing in training and resources, healthcare organizations create an environment that fosters patient-centered communication, engagement, and satisfaction. Patient-centered care not only improves health outcomes but also enhances patient experiences, empowers individuals to actively participate in their own care, and ultimately leads to a healthcare system that revolves around the needs and well-being of the patients it serves.